The Presence and Potential Role of ALDH1A2 in the Glioblastoma Microenvironment - Stephanie Sanders (Cells, 2021)
Glioblastoma (GBM) is the most aggressive malignant glioma. Therapeutic targeting of GBM is made more difficult due to its heterogeneity, resistance to treatment, and diffuse infiltration into the brain parenchyma. Better understanding of the tumor microenvironment should aid in finding more effective management of GBM. GBM-associated macrophages (GAM) comprise up to 30% of the GBM microenvironment. Therefore, exploration of GAM activity/function and their specific markers are important for developing new therapeutic agents. In this study, we identified and evaluated the expression of ALDH1A2 in the GBM microenvironment, and especially in M2 GAM, though it is also expressed in reactive astrocytes and multinucleated tumor cells. We demonstrated that M2 GAM highly express ALDH1A2 when compared to other ALDH1 family proteins. Additionally, GBM samples showed higher expression of ALDH1A2 when compared to low-grade gliomas (LGG), and this expression was increased upon tumor recurrence both at the gene and protein levels. We demonstrated that the enzymatic product of ALDH1A2, retinoic acid (RA), modulated the expression and activity of MMP-2 and MMP-9 in macrophages, but not in GBM tumor cells. Thus, the expression of ALDH1A2 may promote the progressive phenotype of GBM.